Individual structure of psychophysiological functions in connection with competitive performance in the Paralympic sprint on the example of a high-skilled student with visual impairment - Е. И. Чайка; Ж.Л. Козина; В. А. Коробейник; Т. А. Базылюк (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
The purpose of the work is to determine the factor structure of psycho-physiological indicators in correlation with individual performance in athletics sprint in high-qualified athletes with visual impairment on the example of an elite athlete. Material and methods. The study involved a high-qualified athlete, specializing in short-distance running and long jump, the European Athletics Champion 2010; prize winner of the World Paralympic and Paralympic Games among athletes with visual impairments (T12 category) in 2016. Psychophysiological testing of the athlete took place in the corresponding optical lenses. Individual characteristics of the psychophysiological state and results in running for short distances were analyzed. The results in the race were recorded in training, as well as in official and unofficial competitions. A total of 36 results were analyzed. 1 day before the start, psychophysiological indicators were recorded using the computer program "Psychodiagnostics" and similar programs for psychophysiological testing. Results. It was revealed that in athletes with visual impairment the influence of psychophysiological factors as compensatory mechanisms of limited visual possibilities is increased. The obtained data testify to the ability of the examined athlete to prolonged operation of the nervous system. This indicates the strength of the nervous system athletes. This is due to the development of compensatory mechanisms of insufficiency of the visual analyzer. This quality is especially evident for distances of 200 m and 400 m. Conclusions. Compensatory mechanisms of visual deficiency have been identified to maintain high speed in short-distance running as psychophysiological functions: indicators characteristic of sprinters (speed of simple reaction and motility of the nervous system) and specific indicators (efficiency, strength of the nervous system).